Shell-Filling Effects in Circular Quantum Dots. Issue 1 (1998) - Macucci, M.; Hess, Karl
Abstract : We investigate the dependence of the capacitive energy associated with a circular quantum dot on the number of electrons in the dot and on the parameters defining the potential confinement. Our results reproduce the shell-filling behavior that has recently been experimentally observed and allow us to estimate the shape of the confinement potential and the dot size of the experiments.